An update on the use of transdermal oxybutynin in the management of overactive bladder disorder. (April 2016) - Cohn, Joshua A.; Brown, Elizabeth T.; Reynolds, W. Stuart; Kaufman, Melissa R.; Milam, Douglas F.; Dmochowski, Roger R.
Antimuscarinic medications are used to treat nonneurogenic overactive bladder refractory to nonpharmacologic therapy. Side effects such as dry mouth, constipation, blurred vision, dizziness, and impaired cognition limit the tolerability of therapy and are largely responsible for high discontinuation rates. Oxybutynin is a potent muscarinic receptor antagonist whose primary metabolite after first-pass hepatic metabolism is considered largely responsible for its associated anticholinergic side effects. Transdermal administration of medications bypasses hepatic processing. Specifically with oxybutynin, whose low molecular weight permits transdermal administration, bioavailability of the parent drug with oral administration is less than 10%, whereas with transdermal delivery is a minimum of 80%. The result has been an improved side effect profile in multiple clinical trials with maintained efficacy relative to placebo; however, the drug may still be discontinued by patients due to anticholinergic side effects and application site reactions. Transdermal oxybutynin is available as a patch that is changed every 3–4 days, a gel available in individual sachets, or via a metered-dose pump that is applied daily. The transdermal patch was briefly available as an over-the-counter medication for adult women, although at this time all transdermal formulations are available by prescription only.